2(f-59)=54

Simple and best practice solution for 2(f-59)=54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(f-59)=54 equation:



2(f-59)=54
We move all terms to the left:
2(f-59)-(54)=0
We multiply parentheses
2f-118-54=0
We add all the numbers together, and all the variables
2f-172=0
We move all terms containing f to the left, all other terms to the right
2f=172
f=172/2
f=86

See similar equations:

| 15=h+13 | | 7u+7=98 | | -4-2x^2=-102 | | 6y=8y-8 | | e+20=13 | | 16=m/8 | | 21=1i | | k(-7/2)=23/5 | | a/4-2=1 | | r/23=56 | | 6+3x+2x+11+13x-3+5x+10+60=360 | | x+6(x−1)=7(3+x) | | 96=2w+70 | | 2y=0.25+6 | | 79=t+22 | | 8=c-48/4 | | h÷5-(-19)=24 | | 130+20x=300 | | 2y=0.25=6 | | 3y+5y=1740 | | 9=h-28/7 | | 75m=300 | | 6x—6=3x | | /–2x–4+5x=8 | | 6=h-19/8 | | 4x−2=12 | | 76=76s | | 2(3-2x)=54 | | 1=y-86/8 | | m-28=32 | | 12-8=5x+13 | | 60x+40=460 |

Equations solver categories